Sire Evaluation Based on First Lactation 305 Day Milk Yield and Monthly Part Lactation Records in Sahiwal Cattle - Mundhe, U. T.; Gandhi, R. S.; Das, D. N.; Dongre, V. B.; Singh, Arun Pratap (International Journal of Livestock Research, 2018)
A total of 476 milk yield records of Sahiwal cows maintained at National Dairy Research Institute (NDRI) Karnal over a period of 51 years (1961-2011) were investigated and among which 371 animals completed their 305 days lactation length were used for the study, which are daughters of 51 sires with five or more progenies per sire. Sahiwal sires were evaluated on the basis of actual, predicted 305-DMY, expected breeding value based on 1st -3rd monthly part lactation milk yield records, expected breeding value based on 1st -6th and 1st -10th monthly part lactation milk yield records. It was inferred that the ranking of sires on the basis of FL305-DMY was significantly different from other criteria of selection.